Imagined Archaeology and Enlivening the Proximate Senses in the construction of Blind Torrent – An Interdisciplinary Screendance Project - Way, Ruth Margaret; Frampton, Russell James (The International Journal of Screendance, 2016)
The screendance project Blind Torrent, is the result of an ongoing collaborative and interdisciplinary film making process between visual artist Russell Frampton and choreographer and somatic movement practitioner Ruth Way. The article will provide an analysis of the creative processes and insights, which informed Blind Torrent. Anthropological and phenomenological theory will be drawn upon with the aim to reveal how the construction of ‘filmic ritual landscapes’ unearthed connections between site, artifact, temporality and embodied choreographic response. Connections between this screendance practice and the genres of land art and site-specific art will be discussed and inform the contextual analysis. The article will principally examine how the creation of empathic movement responses to the landscape developed a phenomenological interface between the body and landscape to enhance the proximate senses in the construction of Blind Torrent.